2015
DOI: 10.1007/s13277-015-4186-4
|View full text |Cite
|
Sign up to set email alerts
|

IL-6/NOS2 inflammatory signals regulate MMP-9 and MMP-2 activity and disease outcome in nasopharyngeal carcinoma patients

Abstract: The role of nitric oxide (NO)• in the development of the metastatic properties of nasopharyngeal carcinoma (NPC) is not fully understood. Previous studies proposed that interleukin-6 (IL-6) would act as regulator of matrix metalloprotease activation in NPC. Recently, we showed that (NO)• was a critical mediator of tumor growth in patients. The aim of this study was to determine the implication of IL-6 in the progression of NPC pathology via MMPs activation and their possible correlation with (NO)• production. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 63 publications
(70 reference statements)
2
20
0
Order By: Relevance
“…When analyzing our overall data, we observed an association between good prognosis and HPV positivity, whereas adverse prognosis was associated with increasing both CRP levels and WBC counts. These are expected associations that have been described in previous studies [ 9 , 21 , 22 , 23 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 78 ] and therefore suggest that our patient cohort is representative. Furthermore, histopathological features like tumor lymphocyte density predict prognosis both in HPV-negative and HPV-positive oropharyngeal cancer patients [ 79 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…When analyzing our overall data, we observed an association between good prognosis and HPV positivity, whereas adverse prognosis was associated with increasing both CRP levels and WBC counts. These are expected associations that have been described in previous studies [ 9 , 21 , 22 , 23 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 78 ] and therefore suggest that our patient cohort is representative. Furthermore, histopathological features like tumor lymphocyte density predict prognosis both in HPV-negative and HPV-positive oropharyngeal cancer patients [ 79 ].…”
Section: Discussionsupporting
confidence: 85%
“…Several previous studies have shown that both increased systemic CRP levels [ 8 , 47 , 48 , 49 , 50 , 51 , 52 ] and IL6 levels [ 9 , 21 , 22 , 23 , 53 , 54 , 55 , 56 , 57 ] are associated with an adverse prognosis in HNSCC. IL6 can function as a driver of the acute phase reaction, i.e., increased CRP levels can at least partly be due to an IL6 effect [ 1 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matrix metalloproteinases (MMPs) play an important role in the process [ 30 ]. MMP-2 and -9 have been reported to be related with the metastasis of NPC [ 31 , 32 ]. Consistently, the mRNA and protein expression levels of MMP-2/9 were upregulated in NPC cells ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…304 Besides, IL-6 is able to reduce cell adherence toward laminin and stimulates the expression of MMP-2 and MMP-9, leading to metastasis of NPC. [305][306][307] It is hoped that the emergence of targeted therapies against CSCs and EMT might bring about clinical benefits. However, continued study is still imperative in order to attain the goal of understanding the molecular expression profile together with the characteristics of signal pathways in CSCs.…”
Section: Discussionmentioning
confidence: 99%